2006
DOI: 10.1109/twc.2006.1611099
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of distributed space-time coding systems with one and two non-regenerative relays

Abstract: We propose a distributed space-time coding (DSTC) systems based on the Alamouti design. We discuss the limitations in the relay channel of the "out of the box" Alamouti scheme and the additional complexity required to overcome its loss of diversity. Using a bit error rate based antenna selection approach, we design DSTC systems with one regenerative relay that improve on the classical Alamouti scheme when utilized in a two-hop channel. We prove that the proposed one relay DSTC system collects the full diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…None of the above pioneer work allow relays to adaptively adjust their transmit powers according to channel magnitude information, and this is exactly the concern of this paper. Several related work can be found in [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…None of the above pioneer work allow relays to adaptively adjust their transmit powers according to channel magnitude information, and this is exactly the concern of this paper. Several related work can be found in [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of various TDMA-based relaying protocols in a system with one source, relay and destination was analyzed in [7]. A distributed space-time coding technique was proposed for a system with one or two assisting relays in [8,9]. It was shown that this design achieves a diversity gain over a point-to-point system with the same bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…Those relays were called blind relays. As a result, the amplifying coefficients of the relays were fixed numbers and the amplifiers at the relays might go into saturation when the instantaneous gains of the first-hop channels were large [7]. In practical systems, it is more preferable to implement CSI-assisted relays which know the instantaneous channel gains of the first-hop channels.…”
Section: Introductionmentioning
confidence: 99%
“…Laneman et al have proposed an amplifying coefficient for the CSI-assisted relays [1]. It can successfully avoid saturations of the amplifiers [7] and has been used in many previous publications [8], [9]. It is practically very important to analyze distributed Alamouti's code in cooperative networks with CSIassisted relays.…”
Section: Introductionmentioning
confidence: 99%